Cost-Effectiveness Analysis of Antiviral Therapy for Untreated Minimally Active Chronic Hepatitis B to Prevent Liver Disease Progression - Lee, Hankil (Clin Transl Gastroenterol, 2021)
Antiviral therapy (AVT) for chronic hepatitis B (CHB) can prevent liver disease progression. Because of its stringent reimbursement criteria, significant numbers of patients with untreated minimally active (UMA)-CHB exist, although they are still subject to disease progression. We thus performed a cost-effectiveness analysis to assess the rationale for AVT for UMA-CHB. METHODS: We compared cost and effectiveness (quality-adjusted life years, QALYs) in virtual UMA-CHB cohorts of 10,000 50-year-olds receiving AVT (scenario 1) vs no treatment (scenario 2) for 10 years. A Markov model, including 7 health states of CHB-related disease progression, was used. Values for transition probabilities and costs were mostly obtained from recent South Korean data. RESULTS: The simulation of AVT vs no treatment predicted $2,201 incremental costs and 0.175 incremental QALYs per patient for 10 years, with an incremental cost-effectiveness ratio (ICER) of $12,607/QALY, suggesting cost-effectiveness of AVT. In sum, if 10,000 patients received AVT, 720 incident hepatocellular carcinoma and 465 CHB-related more deaths could be averted in 10 years relative to no treatment. When the simulated analysis period was extended to 20 years, AVT was also highly cost-effective with an ICER of $2,036/QALY. Although hepatocellular carcinoma–related mortality was a major factor influencing ICER, its fluctuation can be accepted within willingness to pay of $33,000 in South Korea. According to probabilistic sensitivity analysis with the threshold of willingness to pay, the probability of AVT cost-effectiveness was 83.3%. DISCUSSION: Long-term AVT for patients with UMA-CHB may contribute positively toward individual clinical benefit and national health care budget.